Why do some insider CEOs make more strategic changes than others? The impact of prior board experience on new CEO insiderness - Zhu, Qi; Hu, Songcui; Shen, Wei (Strategic Management Journal, 2020)
Abstract Research Summary This study draws attention to the impact of prior board experiences on the variation in new insider CEOs' degree of “insiderness” in terms of commitment to the status quo and their propensity to make strategic change. We theorize and find that new insider CEOs' prior board experience at the focal firm has a negative effect on strategic change, whereas their prior board experience at other firms has a positive effect. Moreover, the positive effect of prior board experience at other firms is stronger (weaker) for new insider CEOs who have less (more) prior board experience at the focal firm. Our study contributes to upper echelons theory and research on new CEOs, and has important implications for organizational practices regarding CEO succession and strategic change. Managerial Summary Although new insider CEOs tend to make less strategic changes than new outsider CEOs, some of them do make more than others. Our study focuses on new insider CEOs' prior board experiences to explain the difference in their tendency to make strategic change. We find that new insider CEOs who have greater prior experience on the focal firm's board make less strategic changes, whereas those who have greater prior experience on the boards of other firms make more strategic changes. Moreover, our analysis shows that new insider CEOs who have both a high level of prior board experience at other firms and a low level of prior board experience at the focal firm make the most strategic changes.